Capital Tax Competition with Inefficient Government Spending - Wolfgang Eggert (University of Konstanz, Center of Finance and Econometrics (CoFE), 1999)
Models of international tax competition typically assume the existence of a benevolent government. This paper presents a model which integrates the view of government as source of inefficiency with an analysis of distorting taxes on capital investment, savings and labor income in a common theoretical framework. The model yields the conclusion that the effects of international tax coordination on the welfare of residents can be ambiguous because the costs of inefficient public good supply are lowered but wateful government consumption is increased. However, the above finding is derived when the residence-based capital tax is not available. In contrast, government use of taxes clearly is inefficient from the viewpoint of residents in the presence of residence-based capital taxation.
urn:nbn:de:bsz:352-opus-4221
Keywords: H1; H2; 330; Steuerwettbewerb; Leviathan-Modell; Internationale Wirtschaftspolitik; Staatsversagen; Wohlfahrtsanalyse; Theorie